Management of Splenic Artery Aneurysms during Pregnancy - Akkapulu, Nezih; Karakoç, Derya (Acta Medica, 2020)
Splenic artery aneurysms are considered rare; however, they are the most common visceral artery aneurysm in reality. The incidence of splenic artery aneurysm (SAA) increases in pregnancy and may result in significant maternal and fetal mortality if that would develop. This review summarizes etiologic, clinical, and diagnostic features and management of splenic artery aneurysms during pregnancy in the light of recent literature.